Willingness and Access to Joint Replacement Among African American Patients With Knee Osteoarthritis: A Randomized, Controlled Intervention12. Issue 5 (23rd April 2013) - Ibrahim, Said A.; Hanusa, Barbara H.; Hannon, Michael J.; Kresevic, Denise; Long, Judith; Kent Kwoh, C.
Abstract Objective African American patients are significantly less likely to undergo knee replacement for the management of knee osteoarthritis (OA). Racial difference in preference (willingness) has emerged as a key factor. This study was undertaken to examine the efficacy of a patient‐centered educational intervention on patient willingness and the likelihood of receiving a referral to an orthopedic clinic. Methods A total of 639 African American patients with moderate‐to‐severe knee OA from 3 Veterans Affairs primary care clinics were enrolled in a randomized, controlled trial with a 2 × 2 factorial design. Patients were shown a knee OA decision‐aid video with or without brief counseling. The main outcome measures were change in patient willingness and receipt of a referral to an orthopedic clinic. Also assessed were whether patients discussed knee pain with their primary care provider or saw an orthopedic surgeon within 12 months of the intervention. Results At baseline, 67% of the participants were definitely/probably willing to consider knee replacement, with no difference among the groups. The intervention increased patient willingness (75%) in all groups at 1 month. For those who received the decision aid intervention alone, the gains were sustained for up to 3 months. By 12 months postintervention, patients who received any intervention were more likely to report engaging their provider in a discussion about knee pain (92% versus 85%), to receive a referral to an orthopedic surgeon (18% versus 13%), and for those with a referral, to attend an orthopedic consult (61% versus 50%). Conclusion An educational intervention significantly increased the willingness of African American patients to consider knee replacement. It also improved the likelihood of patient–provider discussion about knee pain and access to surgical evaluation.